Validation and adaptation of the mathematic self-efficacy scale for children in Northeast Mexico - Garcia García, Joel; Sánchez Miranda, Martha Patricia; Muñiz García, Manuel Guadalupe (IE Revista de Investigación Educativa de la REDIECH, 2021)
The implementation of educational policies at the national level in Mexico has opened the opportunity for identifying metacognitive aspects that can be measured in primary education. The aim of this study is to adapt and validate a mathematical self-efficacy scale for primary school students in 5th and 6th grades. The sample was of 571 students (294 men and 277 women) with ages between 9 and 13 years of urban and rural schools in Northern Mexico. The scale presented adequate values (a = .77, KMO = .83, Xi2 = 784,688, df = 15, p < .001, S = 47.23%), in addition to confirmatory results that indicate good goodness of fit (CMIN/DF = 2.45, GFI = .98, CFI = .98, RMSEA = .05), because of the above, it is viable for its application in primary schools to know the beliefs of self-efficacy in Mathematics and its influence on the mathematical performance of students.